Pengaruh Store Atmosphere, Cita Rasa, dan Word of Mouth Terhadap Keputusan Pembelian Pada Warung Ikan Bakar Kubu Wisata Serangan - Yagastama, I Kadek Yana; Wimba, I Gusti Ayu; Puja, I Made Suasti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the influence of store atmosphere, taste and word of mouth partially and simultaneously on purchasing decisions. This study was conducted at the Kubu Wisata Serangan Grilled Fish Stall with a sample of 100 people with a sample determination technique using purposive sampling. The research methods used are quantitative research methods with data analysis techniques, namely Instrument Tests, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t Test and F Test. Based on the calculation results each variable partially has a positive and significant influence with the calculated value for the store variable t-count 11.895 > 1.984 with sig. 0.000 < 0.05, taste variable t count 3.193 > 1.984 with sig. 0.002, word of mouth t-count 2.127 > 1.984 with sig. 0.036, and simultaneously have a positive and significant effect with a calculated F value of 294.505 > 2.70 with a sig. 0.000. It is expected to be able to add information about how to order food, cook fish so that it is evenly cooked, add menus at affordable prices and add menu variations and provide satisfaction to consumers.Keywords: Store Atmosphere ; Taste; Word of Mouth ; Purchasing Decisions